Arthur and the nerves of steal - Krensky, Stephen; Akiyama, Bruce (New York : Little, Brown, 2004)
When Buster impulsively drops a Cybertoy into Arthur's backpack in the drugstore one day, he feels so guilty that he finally confesses to his friend and they try to return the popular toy before anyone else finds out.
Accelerated Reader AR
Keywords: Shoplifting -- Fiction; Rabbits -- Fiction; Aardvark -- Fiction; Animals -- Fiction